To translate the point \( C = (-5, 1) \) horizontally by \(-4\) and vertically by \(+3\), we can apply the translation to the coordinates of point \( C \).
-
Horizontal translation:
- Move \( C \) horizontally by \(-4\): \[ x' = -5 + (-4) = -5 - 4 = -9 \]
-
Vertical translation:
- Move \( C \) vertically by \(+3\): \[ y' = 1 + 3 = 4 \]
Now, combining these translations, the new coordinates \( C' \) will be: \[ C' = (-9, 4) \]
Thus, the coordinates of \( C' \) after the translation are \(\boxed{(-9, 4)}\).